A review on advanced catalytic co-pyrolysis of biomass and hydrogen-rich feedstock: Insights into synergistic effect, catalyst development and reaction mechanism. (August 2020) - Ahmed, Mohamed H.M.; Batalha, Nuno; Mahmudul, Hasan M.D.; Perkins, Greg; Konarova, Muxina
Graphical abstract: Highlights: Catalytic co-pyrolysis of biomass and high-rich feedstock is reviewed. Synergistic interaction between hydrogen donor feedstock and biomass are presented. Effective catalysts for biomass deoxygenation and hydrogen transfer are compared. Co-pyrolysis addresses waste management goals by utilizing abundant waste feedstock. Abstract: The depletion of fossil fuel reserves and the growing demand for alternative energy sources are the main drivers of biomass and carbonaceous waste utilization. Particularly, non-edible lignocellulosic biomass is the most attractive renewable feedstock due to its abundance. Pyrolysis of biomass produces highly oxygenated compounds with oxygen content >35 wt%. The cost-effective elimination of oxygen from the pyrolysis oil is the most challenging task impeding the commercialization of biomass to biofuel processes. The effective hydrogen/carbon ratio in biomass pyrolysis oil is low (0.3), requiring external hydrogen supply to produce hydrocarbon-rich oils. Exploiting hydrogen-rich feedstock particularly, solid waste (plastic, tyre and scum) and other low-cost feedstock (lubricant oil, methane, methanol, and ethanol) offer an eco-friendly solution to upgrade the produced bio-oil. Multi-functional catalysts that are capable of cleaving oxygen, promoting hydrogen transfer and depolymerisation must be developed to produce hydrocarbon-rich oil from biomass. This review compares catalytic co-pyrolysis studies based on zeolites, mesoporous silica and metal oxides. Furthermore, a wide range of catalyst modifications and the role of each feedstock were summarised to give a complete picture of the progress made on biomass co-pyrolysis research and development.